2017
DOI: 10.1021/acscatal.7b02036
|View full text |Cite
|
Sign up to set email alerts
|

Ordering and Phase Control in Epitaxial Double-Perovskite Catalysts for the Oxygen Evolution Reaction

Abstract: The complex oxide compound praseodymium barium cobalt oxide (PBCO) is an efficient catalyst for the oxygen evolution reaction (OER) during electrochemical water splitting, with an activity that is mainly ascribed to PBCO's inherent atomic structure and band alignment. Here, we report on epitaxial PBCO thin films showing electrocatalytic properties, with current densities of up to 10 mA/cm 2 at 1.8 V vs RHE. Dense PBCO thin films are synthesized in a disordered perovskite phase as well as in a coherently oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 68 publications
4
50
0
Order By: Relevance
“…For one, epitaxial growth processes such as PLD allow to stabilize materials and phases away from thermodynamic equilibrium. In this way, for example, coherently ordered chains of oxygen vacancy defects have been controlled and stabilized in epitaxial double-perovskite OER catalysts, such as described in [13]. As could be shown, catalytic activity and overpotential of these compound is primarily decoupled from its polymorphous phase.…”
Section: Generation Of Propertiesmentioning
confidence: 94%
See 3 more Smart Citations
“…For one, epitaxial growth processes such as PLD allow to stabilize materials and phases away from thermodynamic equilibrium. In this way, for example, coherently ordered chains of oxygen vacancy defects have been controlled and stabilized in epitaxial double-perovskite OER catalysts, such as described in [13]. As could be shown, catalytic activity and overpotential of these compound is primarily decoupled from its polymorphous phase.…”
Section: Generation Of Propertiesmentioning
confidence: 94%
“…In recent literature, it was shown that it is possible to synthesize e.g. SrIrO 3 or (Pr,Ba)CoO 3−δ layers with a surface roughness below 2 nm at a layer thickness of about 100 nm [2,13], while even subnanometer surface smoothness was achieved for (La,Sr)CoO 3−δ at a similar thickness [14]. The growth process can be monitored and controlled by means of electron diffraction techniques allowing layer deposition with single monolayer precision.…”
Section: Model Systems With Defined Structural Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Perovskite oxides (ABO 3 ), which incorporate rare‐earth cations (A‐site) and transition metal cations (B‐site), have been recognized as potential alternatives noble‐metal electrocatalysts owing to its high ionic and structure flexibility . In previous studies, LaCoO 3 (LCO) was found to be a durable and active OER catalyst .…”
Section: Introductionmentioning
confidence: 99%